Importance of Corporate Vision - Suranga, J.M. (University of Sri Jayewardenepura, Nugegoda., 2014)
The business environment of today is characterized as both dynamic and complex. As a result of that, commercial organizations face fierce competition on all fronts. To deal with strategic planning in this businesses environment has become difficult and corporate vision has been discussed as a major concept which is needed for survival and growth. Formulating of a corporate vision is considered as the first step of the strategic management process. This research paper discusses theoretical and empirical research findings about the corporate vision and how researchers did identify its importance.
Keywords: Corporate Vision; Strategic Intent; Corporate Visioning; Strategic Management